2014
DOI: 10.1159/000360543
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characteristics of the Inhibitory Effects of Docosahexaenoic Acid on Vascular Contractions Studied in Rat Mesenteric Artery

Abstract: Background/Aims: Effects of docosahexaenoic acid (DHA) on blood vessel contractions to various constrictors were investigated in rat mesenteric artery and compared with those of eicosapentaenoic acid (EPA) and linoleic acid (LA). Methods: Tension changes in mesenteric ring segments were isometrically recorded. Results: On sustained contractions induced by a thromboxane A2 mimetic (U46619), DHA exerted a strong inhibitory effect. This inhibitory effect of DHA on U46619 appeared both in endothelium-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…These beneficial vascular effects are most likely not mediated by MUFA since oleic acid is reported to inhibit the endothelium-dependent vasodilator response to acetylcholine in rabbit femoral artery [ 68 ] and to decrease endothelial nitric oxide synthase (eNOS) activity in cultured endothelial cells [ 69 ]. On the contrary, supplementation with omega-3 fatty acids is reported not only to reduce arterial contraction [ 70 , 71 , 72 , 73 ], but also to improve endothelium-dependent relaxation [ 74 , 75 , 76 , 77 , 78 ]. Our results agree with those of Farooq et al, which show that omega-3 supplementation reverts the impairment of endothelium-dependent relaxation, the increase in angiotensin AT-1 receptor expression and the oxidative stress induced by aging in rat mesenteric arteries [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial vascular effects are most likely not mediated by MUFA since oleic acid is reported to inhibit the endothelium-dependent vasodilator response to acetylcholine in rabbit femoral artery [ 68 ] and to decrease endothelial nitric oxide synthase (eNOS) activity in cultured endothelial cells [ 69 ]. On the contrary, supplementation with omega-3 fatty acids is reported not only to reduce arterial contraction [ 70 , 71 , 72 , 73 ], but also to improve endothelium-dependent relaxation [ 74 , 75 , 76 , 77 , 78 ]. Our results agree with those of Farooq et al, which show that omega-3 supplementation reverts the impairment of endothelium-dependent relaxation, the increase in angiotensin AT-1 receptor expression and the oxidative stress induced by aging in rat mesenteric arteries [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the decreased production of prostanoids, in arteries from orchidectomized rats fed the DHA-diet, indomethacin did not modify the ACh-induced response, which could be attributed to that DHA could reduce the sensitivity of the smooth muscle to prostanoids [ 59 , 60 ]. More surprising was the effect of DHA-diet in control rats, in which an increase in the Ach response in presence of indomethacin was observed, indicating the prevalence of a net vasoconstrictor effect of prostanoids.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, our previous studies on rat thoracic aorta and mesenteric artery showed that LA (3 × 10 −5 M) did not affect the contractions elicited by U46619, PGF 2α , phenylephrine, and 80 mM-KCl solution. 31,32) At present, we do not have a rationale to explain the discrepant results between blood vessels (rat aorta and mesenteric artery) and LGI tract LSMs (guinea pig ileum and colon). However, the following explanations might be possible: 1) Inhibition of VGCCs/ VDCCs: LA (5 µM) was reported to inhibit the I Ca in rat ventricular myocytes and LA (10-30 µM) was reported to inhibit the I Ca in rabbit distal ileal LSMs.…”
Section: Discussionmentioning
confidence: 92%